Endogenous Green Preferences - Ravi Vora; Guglielmo Zappala (CESifo GmbH, 2025)
Stringent environmental policies often lack public support. But after policies are enacted, do individual preferences about them change? Using surveys covering 38 countries around the world, we study the effect of exposure to environmental policies on policy preferences. Exploiting within-country-year, across birth-cohort variation, we find that individuals exposed to more stringent environmental policies during early adulthood are more supportive of environmental policies later on in life. This relationship suggests that a society's environmental policy attitudes evolve endogenously, with implications for forecasting the path of these economic measures, as well as for how to evaluate their normative appropriateness.
Keywords: D72; D83; H23; H31; Q58; 330; endogenous preferences; environmental policy; environmental preferences; experience; formative age; policy support.